Aerothermodynamic study of Two-Stage-To-Orbit system composed of wide-speed-range vehicle and rocket. (June 2021) - Cheng, Jiaming; Chen, Rongqian; Qiu, Ruofan; Sun, Weiqiang; You, Yancheng
Abstract: Hypersonic vehicles with Mach numbers greater than five exhibit complex shock wave interactions, accompanied by locally enhanced heat flux near the shock-affected surface. To investigate the unclear interstage thermal environment in a Two-Stage-To-Orbit system, a model composed of a wide-speed-range vehicle and a reusable rocket is employed in an aerothermodynamic study of the Two-Stage-To-Orbit system considering the interstage interactions performed at freestream Mach number = 6. The innovations of this paper are the complex model, which is highly similar to the real situation, and the study of the thermal environment between stages near different reflection positions, whereby the shock wave interference that causes different forms of heat flux is divided into two categories. The thermal design of the Two-Stage-To-Orbit system should especially consider the head of the wide-speed-range vehicle, interstage distance, and the swept angle of canted fins and wings, as well as their width. This paper adopts the second-order AUSMDV (a variant of the Advection Upstream Splitting Method) scheme for spatial discretization and Lower–Upper Symmetric Gauss–Seidel method for time discretization in formulating the Reynolds-averaged Navier–Stokes equations, which are then solved by the finite volume method and Menter's shear stress transport k- ω turbulence model. Numerical analysis sheds light on the complex shock structure and the reasons for the considerable increase in wall temperature and aerothermal loads at critical parts of various reflected shock positions. The incident shock wave generated by the head apex of the rocket constantly reflects and gradually weakens between the two stages, which brings about shock wave/boundary-layer interaction and gives rise to elevated heat flux. The moderate incident shock and the weak reflected shock are primarily responsible for the lack of boundary-layer separation, although the expansion caused by the convex curvature of the head of the wide-speed-range vehicle also contributes. A non-reflected part of the incident shock wave interacts with the windward surface of the canted fins and wings, producing shock wave/boundary-layer interaction and a V-shaped heat flux distribution that extends to the leading edges of the wings. As the angle of attack decreases, the intensity of the incident shock and the reflected shock gradually weakens, leading to reduced heat flux on the windward surface of the wide-speed-range vehicle. The range over which the incident shock impinges the walls also narrows, corresponding to the smaller heat flux distribution. These aerothermal studies comprehensively determine the law of thermal changes, which is significant for the design of thermal protection in Two-Stage-To-Orbit systems. Highlights: The interstage thermal environment of real parallel vehicle is studied. The shock wave causes different forms of heat flux at various reflection positions. The shock wave interaction is divided into two categories. The incident shock wave reflects between stages, leading to elevated heat flux. A non-reflected part of the incident shock causes a V-shaped heat flux distribution.